Valley girl [videorecording (DVD)] - Goldenberg, Rachel Lee; Rothe, Jessica; Whitehouse, Josh, 1990-; Ennis, Jessie (Warner Bros. Home Entertainment, 2020)
Jukebox musical about two teenagers from different backgrounds who fall in love during the early 1980s.